PROFILE OF THE SERVICE OFFERED TO THE ELDERLY BY PILATES ESTABLISHMENTSO (Fiep Bulletin - online, 2019)
Introduction: In the past decade there has been a considerable increase in the number of establishments that offer the Pilatesmethod as a treatment option or for the improvement of physical conditioning. Pilates may provide several benefits to the elderlypopulation, and the demand for professionals specializing in this population is growing. Objectives: To delineate the profile of theservice offered to the elderly by Pilates establishments in the city of Vitória/ES/Brazil. Methodology: Transversal descriptive studythat interviewed professionals in charge of Pilates establishments in the neighbourhoods of Jardim da Penha and Mata da Praia.The data was analysed through descriptive statistics, frequency and percentage (qualitative data), average, minimum value,maximum value (quantitative data). Results: Fifteen establishments partook in the study, most of which labelled themselves asPilates studios; 40% cater for 70 individuals a month, distributed in groups of two to four an hour; the age of patients/clients variedfrom 10 to 95 years old, 41.3% of them being over 60. All of the establishments employ a physiotherapist and 46.7% of them alsoemploy physical education graduates who utilise the Pilates method. Payment for the service is made privately, normally everymonth, and the amount varies according to the number of weekly sessions. Different modalities are offered, with a particularemphasis on clinical/therapeutic Pilates. Conclusions: There are a considerable number of establishments that offer the Pilatesmethod in the neighbourhoods comprised in this study, but most do not seem to offer an exclusive service directed to the elderly.On the other hand, many professionals seek to keep themselves updated in the different modalities of the method.
Keywords: Pilates; Service; Elderly